-9(x-2)=-2(6+x)+3x

Simple and best practice solution for -9(x-2)=-2(6+x)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(x-2)=-2(6+x)+3x equation:



-9(x-2)=-2(6+x)+3x
We move all terms to the left:
-9(x-2)-(-2(6+x)+3x)=0
We add all the numbers together, and all the variables
-9(x-2)-(-2(x+6)+3x)=0
We multiply parentheses
-9x-(-2(x+6)+3x)+18=0
We calculate terms in parentheses: -(-2(x+6)+3x), so:
-2(x+6)+3x
We add all the numbers together, and all the variables
3x-2(x+6)
We multiply parentheses
3x-2x-12
We add all the numbers together, and all the variables
x-12
Back to the equation:
-(x-12)
We get rid of parentheses
-9x-x+12+18=0
We add all the numbers together, and all the variables
-10x+30=0
We move all terms containing x to the left, all other terms to the right
-10x=-30
x=-30/-10
x=+3

See similar equations:

| 6+m=40 | | 100x-200=500 | | -22-25+9x=99 | | 10=m/2+3 | | -15×+2y-4=10 | | X+5=20-2x= | | -10n+3(8-8n)=-6(n-4) | | -5x+28=-7x+10 | | w/4-9=11 | | 23=4d+5 | | |x+4|=11 | | (-7+9(y+1))=5y+8 | | x+(3x-4)=5-(2x+4) | | t=0.25Y | | x-3/4=13/4 | | (6x-5)-(4x+5)=180 | | 9+4k+7kk=8 | | n*5=15 | | -3x^2+43x+136=0 | | (2x-3)2-42=0 | | X^2=2z | | 3x/2-4=x-6 | | 3(x-4)=2x+4-6x | | x=2/3=5/3 | | 6x-15=x+8=168 | | 6/5+5m/4=69/20 | | 12 – c = 8  | | 4(x+1)+31=3x | | −5+x2=−9 | | 7/26=21/x | | (2x-7)+(3x-23)=80 | | 2(x-1)=3x+2-2x+6 |

Equations solver categories